The Impact of Fiscal Federalism on Local Governance in Nepal: A Study of Financial Decentralisation - Khanal, Krishna Prasad (Journal of Multidisciplinary Research Advancements, 2026)
This study analyses the impact of fiscal federalism on local governance in Nepal, with a specific focus on the implementation of financial decentralisation following the 2015 constitutional reform. Employing a mixed-methods approach, it integrates quantitative analysis of fiscal data from 2019/20 to 2023/24 with qualitative insights from key informant interviews. The findings reveal that local governments remain critically dependent on federal transfers, generating, on average, only 21% of their revenue internally, thereby constraining genuine fiscal autonomy. Furthermore, stark horizontal imbalances exist, with affluent urban centres such as Kathmandu Metropolitan City accumulating surpluses while rural municipalities, such as Saipal, face severe fiscal deficits, thereby threatening the equity objectives of federalism. Operational challenges, including legislative ambiguities, delayed fund disbursements, weak audit enforcement, and significant capacity deficits at the local level, further impede effective decentralisation. The study concludes that, although the structural framework of federalism is established, its promise of efficient, accountable, and equitable local governance remains constrained. Realising this potential requires integrated policy reforms to enhance local revenue generation, streamline intergovernmental fiscal relations, strengthen accountability mechanisms, and build sustainable administrative capacity.